The gene expression profiling of hepatocellular carcinoma by a network analysis approach shows a dominance of intrinsically disordered proteins (IDPs) between hub nodes1. Issue 11 (13th November 2015) - Singh, Sakshi; Colonna, Giovanni; Di Bernardo, Giovanni; Bergantino, Francesca; Cammarota, Marcella; Castello, Giuseppe; Costantini, Susan
<x xml:space="preserve">Abstract</x> The results evidence a strong presence of intrinsically disordered proteins in key roles as hubs in HCC sub-networks.